Materiality Disclosure in Sustainability Reporting: Evidence from Malaysia - Sie Bing Ngu; Amran, Azlan (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This paper aims to examine the determinants that influence companies to report material sustainability information in their corporate annual reports. Design/Methodology/Approach: To validate the determinants influencing materiality disclosure, content analysis was conducted on the annual reports of the top 113 Malaysian public listed companies in 2016, and the smart partial least squares technique was employed to examine the proposed relationships. Research findings: The empirical results indicate that board activity and board independence play a significant role in the determination of materiality disclosure. The results also reveal that board size, company size, profitability, leverage and industry are insignificant predictors of materiality disclosure. The results indicate that many listed companies in Malaysia disclose some amount of material sustainability information. However, the level of disclosure remains relatively low. Theoretical contribution/Originality: Notwithstanding that materiality is regarded as a key reporting principle in the preparation of sustainability reports, research on the application of the materiality concept in sustainability reporting remains to be an unexplored theme in Malaysia. This work sheds light on materiality disclosure in sustainability reporting of large companies operating in Malaysia through the combined views of the stakeholder and legitimacy theories. Practitioner/Policy implications: The results should be of great interest to policymakers who are concerned with formulating sustainability policies to achieve greater materiality disclosure. It also provides strategic insights to companies that board characteristics, such as board activity and board independence, influence materiality disclosure. Board members are urged to consider the importance of the reporting materiality determination process; otherwise, poor reporting may result in conflict with major stakeholder groups who do not see the material issues disclosed in the sustainability reports. Research limitation/Implications: The results are limited to the context of Malaysia. Future researchers can compare materiality disclosure with other countries, such as Singapore and Thailand, to enrich the sustainability reporting literature. Keywords: Legitimacy Theory, Stakeholder Theory, Materiality, Sustainability Reporting JEL Classification: M41